2021
DOI: 10.1371/journal.pntd.0008492
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance and genetic structure of Aedes aegypti populations from Rio de Janeiro State, Brazil

Abstract: Vector control largely relies on neurotoxic chemicals, and insecticide resistance (IR) directly threatens their effectiveness. In some cases, specific alleles cause IR, and knowledge of the genetic diversity and gene flow among mosquito populations is crucial to track their arrival, rise, and spread. Here we evaluated Aedes aegypti populations’ susceptibility status, collected in 2016 from six different municipalities of Rio de Janeiro state (RJ), to temephos, pyriproxyfen, malathion, and deltamethrin. We coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Similarly, in Brazil (Juazeiro do Norte) [ 74 ], a decrease in resistance to temephos was observed, from a RR of 10.4 to a RR of 7.2, 7 years after this larvicide was replaced by Bacillus thuringiensis israelensis (Bti). Also in Brazil, Rahman et al [ 75 ] observed a reduction in the level of resistance to temephos in Rio de Janeiro, in the municipality of Campos dos Goytacazes, 15 years after discontinuationof its use, from a RR of 7.8 in 2001 to a RR of 2.6 in 2016. These authors also detected a significant decrease in the levels of resistance to temephos in the municipality of Itaperona, from a RR of 25.6 in 2011 to a RR of 7.3 in 2016, after this larvicide was substituted by IGR [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Brazil (Juazeiro do Norte) [ 74 ], a decrease in resistance to temephos was observed, from a RR of 10.4 to a RR of 7.2, 7 years after this larvicide was replaced by Bacillus thuringiensis israelensis (Bti). Also in Brazil, Rahman et al [ 75 ] observed a reduction in the level of resistance to temephos in Rio de Janeiro, in the municipality of Campos dos Goytacazes, 15 years after discontinuationof its use, from a RR of 7.8 in 2001 to a RR of 2.6 in 2016. These authors also detected a significant decrease in the levels of resistance to temephos in the municipality of Itaperona, from a RR of 25.6 in 2011 to a RR of 7.3 in 2016, after this larvicide was substituted by IGR [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in Brazil, Rahman et al [ 75 ] observed a reduction in the level of resistance to temephos in Rio de Janeiro, in the municipality of Campos dos Goytacazes, 15 years after discontinuationof its use, from a RR of 7.8 in 2001 to a RR of 2.6 in 2016. These authors also detected a significant decrease in the levels of resistance to temephos in the municipality of Itaperona, from a RR of 25.6 in 2011 to a RR of 7.3 in 2016, after this larvicide was substituted by IGR [ 75 ]. Consequently, rotating to a new insecticide with a different mode of action could be advantageous in terms of temephos resistance management.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Conde et al [56] observed in Colombia (Caldas) the reduction of temephos resistance from RRs of 13.27 and 11.48 in 2007 to 4.75 and 5.61 in 2011 after discontinuation of its use for four years. Similarly, Brazil (Juazeiro do Norte) [70] observed a decrease in resistance to temephos from a RR of 10.4 to 7.2 after 7 years when this larvicide was replaced by Bacillus thuringiensis israelensis (Bti) and Rahman et al [71] observed in Rio de Janeiro in the municipality of Campos dos Goytacazes the reduction of temephos resistance from a RR of 7.8 in 2001 to 2.6 in 2016 after discontinuation of its use for 15 years and detected signi cant decrease in the levels of resistance to temephos in the municipality of Itaperona from a RR of 25.6 in 2011 to 7.3 in 2016 after this larvicide was substituted by IGR. Consequently, rotating to a new insecticide with a different mode of action could be advantageous for temephos resistance management.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies analyzed Ae . aegypti population genetic structure within cities using nuclear markers such as microsatellites [ 14 21 ] or SNPs [ 20 , 22 25 ]. While most of these works did not focus on the effect of urban heterogeneity on vector’s genomics, those that did showed a clear effect of urban landscape on genetic structure and vector dispersal [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti is key to improve any control strategy. Fine-scale genetic structure can provide critical information about the potential dissemination of alleles associated to insecticide resistance, particularly those of the kdr gene [ 35 , 36 ], and vector competence for different arboviruses [ 7 ]. It also conditions the potential success of vector control programs based on the release of Wolbachia -carrying or genetically modified mosquitoesto limit arboviral transmission [ 37 ].…”
Section: Introductionmentioning
confidence: 99%